Ayahuasca Treatment Center Safety for the Western Seeker. (September 2016) - Ray, Raven Renèe; Lassiter, Kerry S.
Abstract: Ayahuasca, an ancient Amazonian psychedelic tea traditionally used ceremonially among indigenous peoples, has recently become known as a possible treatment for a wide range of disorders. The awareness of this sacred medicine has grown exponentially over the past decade, attracting westerners from a wide variety of backgrounds, hoping to find treatment for a myriad of emotional and physical illnesses, as well as spiritual needs. In the wake of the commercialization and westernization of the use of ayahuasca, and the subsequent proliferation of ayahuasca treatment centers, this paper examines the benefits and possible risks of this form of therapy in an effort to create a safety protocol for Westerners in this context. The most practical approach to increasing safety for Westerners attending these Amazonian treatment centers is to educate the seeker prior to treatment and to provide access to specialized therapeutic aftercare services.